Regional co-operation in East-Central Europe in the Polish foreign policy (Economic and Political Thought, 2015)
With the changes in international order, the role of regional co-operationin East-Central Europe in the Polish foreign policy changed too. In the early1990s, Poland was deeply involved in the development of new structuressuch as the Central European Initiative, the Council of the Baltic Sea States,and the Visegrad Triangle. The new organisations, to a great extend, weretreated instrumentally as a step on the way to rapprochement with the EUand NATO. Poland did not promote its own concepts of developing a newvalue in this part of Europe and did not aspire to play the role of a regionalpower based on the new structures either. After the accession to the EUin 2004, the attention of Polish diplomacy focused on the Visegrad Group(V4), which was a key tool in the co-operation of the four countries – Poland,the Czech Republic, Slovakia and Hungary – in the field of their commoninterests. However, due to big divergences, its role in the areas that arestrategic for the security of the region was of little importance. In essence,the regional co-operation in the East-central Europe was important but fromthe perspective of Warsaw, it was of secondary importance.